2014
DOI: 10.1002/jssc.201401007
|View full text |Cite
|
Sign up to set email alerts
|

Application of high-performance countercurrent chromatography for the isolation of steroidal saponins from Liriope plathyphylla

Abstract: High-performance countercurrent chromatography (HPCCC) with electrospray light-scattering detection was applied for the first time to isolate a spirostanol and a novel furostanol saponin from Liriope platyphylla. Due to the large differences in KD values between the two compounds, a two-step HPCCC method was applied in this study. The primary HPCCC employed methylene chloride/methanol/isopropanol/water (9:6:1:4 v/v, 4 mL/min, normal-phase mode) conditions to yield a spirostanol saponin (1). After the primary H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“…Several preparative‐scale HSCCC studies have been reported, the preparative‐scale HSCCC instruments (850–1200 mL of total volume) were used to separate C3G or C3R from 430 mg to 10 g of enriched anthocyanin extracts or crude plant extracts. In those cases, the rotational speed and flow rate ranges were 700–1000 rpm and 3.0–5.0 mL/min, respectively, and the HSCCC run time was 120–600 min [, ]. The yields of C3G or C3R were dependent on whether the crude sample extracts were semi‐purified by resins or not before CCC run.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several preparative‐scale HSCCC studies have been reported, the preparative‐scale HSCCC instruments (850–1200 mL of total volume) were used to separate C3G or C3R from 430 mg to 10 g of enriched anthocyanin extracts or crude plant extracts. In those cases, the rotational speed and flow rate ranges were 700–1000 rpm and 3.0–5.0 mL/min, respectively, and the HSCCC run time was 120–600 min [, ]. The yields of C3G or C3R were dependent on whether the crude sample extracts were semi‐purified by resins or not before CCC run.…”
Section: Resultsmentioning
confidence: 99%
“…The work presented here demonstrates that HPCCC instruments perform just as well with a natural product extract as with a mixture of standards. Up to now, HPCCC have been used to isolate standard or active molecules from diverse natural sources . It is also demonstrates that volumetric scale‐up between HPCCC instruments also works for a natural product.…”
Section: Introductionmentioning
confidence: 97%
“…To efficiently separate the saponins, HPCCC was applied to yield saponin fractions in the order of the number of sugars linked to the triterpene aglycone. The two‐phase solvent system comprising DM/M/IPA/Wat (9:6:1:4, v / v / v / v ) was used to fractionate the enriched saponin extract because we have demonstrated that the DM/M/IPA/Wat system is suitable for separating and purifying saponins from medicinal herbs such as Dioscorea villosa and Ophiopogon platyphylla . The distribution factor of the enriched saponin extract in the DM/M/IPA/Wat (9:6:1:4, v /v) system was 3.60.…”
Section: Resultsmentioning
confidence: 99%
“…Combination of CCC and HPLC, also named as 2D chromatography, provides an even more robust and versatile methods for separation of complex matrix, which has been increasingly explored in separation of different natural Article Related Abbreviations: CCC, countercurrent chromatography; 1 D, first dimension; 2 D, second dimension. The heart-cut mode of 2D separation has been focused on the optimization of biphasic solvent system, improving of equipment, and the combination with the detector of ESI-MS/NMR spectroscopy [10][11][12][13][14][15][16][17][18]. On-line comprehensive 2D chromatography has been conventionally applied in gas chromatography (GC × GC) and liquid chromatography (LC×LC) and they have been well studied because of their powerful separation efficiency for complex samples [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Up to 2016, 2D CCC separation of complex samples had been conducted only by heart-cut mode, that is to say, a limited number of fractions were collected from 1 D and transferred physically into 2 D separation. The heart-cut mode of 2D separation has been focused on the optimization of biphasic solvent system, improving of equipment, and the combination with the detector of ESI-MS/NMR spectroscopy [10][11][12][13][14][15][16][17][18]. However, the maximum potentiality in 2D chromatography CCC-HPLC with heart-cut mode was limited owing to the low peak capacity [19].…”
Section: Introductionmentioning
confidence: 99%